Longitudinal In Vivo Assessment of Host-Microbe Interactions in a Murine Model of Pulmonary Aspergillosis - Saini, Shweta; Poelmans, Jennifer; Korf, Hannelie; Dooley, James L.; Liang, Sayuan; Manshian, Bella B.; Verbeke, Rein; Soenen, Stefaan J.; Vande Velde, Greetje; Lentacker, Ine; Lagrou, Katrien; Liston, Adrian; et al. (iScience, 2019)
The fungus Aspergillus fumigatus is ubiquitous in nature and the most common cause of invasive pulmonary aspergillosis (IPA) in patients with a compromised immune system. The development of IPA in patients under immunosuppressive treatment or in patients with primary immunodeficiency demonstrates the importance of the host immune response in controlling aspergillosis. However, study of the host-microbe interaction has been hampered by the lack of tools for their non-invasive assessment. We developed a methodology to study the response of the host's immune system against IPA longitudinally in vivo by using fluorine-19 magnetic resonance imaging (19F MRI). We showed the advantage of a perfluorocarbon-based contrast agent for the in vivo labeling of macrophages and dendritic cells, permitting quantification of pulmonary inflammation in different murine IPA models. Our findings reveal the potential of 19F MRI for the assessment of rapid kinetics of innate immune response against IPA and the permissive niche generated through immunosuppression. [Display omitted] •Host-pathogen immune response is visualized in vivo and quantified against IPA•Modified PFC-based nanoparticles were used for in vivo labeling of immune cells•Clinical immunosuppression depict dynamic immune response upon fungal challenge•19F MRI showed follow-up of labeled immune cells in individual animals over time Infection Control in Health Technology; Medical Imaging; Mycology